2005
DOI: 10.1128/aac.49.10.4085-4092.2005
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of the Effect of Antimicrobial Peptides on the Cell Envelope of Escherichia coli

Abstract: The influences of the antibacterial magainin 2 and PGLa from the African clawed frog (Xenopus laevis) and the hemolytic bee venom melittin on Escherichia coli as the target cell were studied by atomic force microscopy (AFM). Nanometer-scale images of the effects of the peptides on this gram-negative bacterium's cell envelope were obtained in situ without the use of fixing agents. These high-resolution AFM images of the surviving and intact target cells before and after peptide treatment showed distinct changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
127
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 35 publications
(39 reference statements)
20
127
0
2
Order By: Relevance
“…The average measured length, width, and height of the untreated cells (n ϭ 23) were 3.42 Ϯ 0.78 m, 1.18 Ϯ 0.18 m and 0.22 Ϯ 0.05 m, respectively. The dimensions of the air-dried E. coli cells reported here compare well with those found in the literature (20,21). E. coli cells were then treated with the minimum concentration of peptide required to inhibit bacterial growth by 50% for a period of 0.5, 2, and 5 h, and imaged.…”
Section: Atomic Force Microscopy Imaging Of Untreated and Amptreated supporting
confidence: 60%
See 1 more Smart Citation
“…The average measured length, width, and height of the untreated cells (n ϭ 23) were 3.42 Ϯ 0.78 m, 1.18 Ϯ 0.18 m and 0.22 Ϯ 0.05 m, respectively. The dimensions of the air-dried E. coli cells reported here compare well with those found in the literature (20,21). E. coli cells were then treated with the minimum concentration of peptide required to inhibit bacterial growth by 50% for a period of 0.5, 2, and 5 h, and imaged.…”
Section: Atomic Force Microscopy Imaging Of Untreated and Amptreated supporting
confidence: 60%
“…Several studies investigating the interaction of cationic AMPs with model bacterial membranes have shown that an overcompensation in zeta potential at high peptide concentrations is associated with membrane insertion via hydrophobic interactions (22)(23)(24). A similar trend was also reported for the interaction of the cationic peptide rBPI 21 with LPS aggregates (24). The overcompensation in E. coli zeta potential at high pepR concentrations (ՆMICs) may indicate: 1) that hydrophobic interactions contribute to membrane interaction in addition to electrostatic attraction, or 2) not all positive charges of pepR contribute to electroneutralization.…”
Section: Journal Of Biological Chemistry 27541supporting
confidence: 56%
“…Meincken et al previously found an increase in the membrane roughness of E. coli cells exposed to Mel [22]. The authors attributed this membrane roughness to an increase in the surface area of the membrane, after Mel incorporation into the outer membrane of the bacterial cell [22]. The ruffled appearance observed in the present study may similarly be caused by peptide integration into the membrane.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, it is likely that the cells exposed to Mel were under enough stress to cause DNA damage. Meincken et al previously found an increase in the membrane roughness of E. coli cells exposed to Mel [22]. The authors attributed this membrane roughness to an increase in the surface area of the membrane, after Mel incorporation into the outer membrane of the bacterial cell [22].…”
Section: Discussionmentioning
confidence: 98%
“…Such an increase in roughness has also been reported for E. coli 057 and the lytic phage A 157 phage-host system (Dubrovin et al, 2008). Further, AFM studies have shown that mechanical and chemical damage of cell surface results in increased roughness-including damage caused by EDTA (Amro et al, 2000), detergents (Camesano et al, 2000), proteases (F Malfatti, unpublished) (Camesano et al, 2000) and antibiotics (Braga and Ricci, 1998;Meincken et al, 2005). Marine phages lyse 10-50% of bacteria production in the upper ocean, and it would be interesting to observe if phage-infected bacteria and archaea could be identified through a surface 'signature'.…”
Section: Bacterial Surface and Morphologymentioning
confidence: 83%